Geophysical and Geotechnical Evaluation of Tanjero Sandstone Layers at Dokan Area Using Ultrasonic Wave Method - Al-Awsi, Munther Dhahir; Khorshid, Salman Z. (Iraqi Journal of Science, 2021)
The aim of this paper is to determine the capability of the ultrasonic technique to predicate and evaluate some elastic and geotechnical properties within sand stone layers. For this purpose, 15 rock samples were collected from Tanjero Formation that is exposed in Dokan area, northeastern Iraq. Elastic wave velocities (Vp and Vs) and density (P) values for rock samples were determined by applying laboratory testing. From Vp, Vs, and density values, the porosity, elastic modulus, and some geotechnical parameters were calculated. The relationship between P wave velocity and elastic properties of samples was derived. Empirical equations were obtained by applying the regression analyses between Vp and the measured elastic properties. Good correlations were found, which may supply a good estimation of elastic properties from velocity information related to the geological setting of the area. This work confirmed the capability of the ultrasonic technique for predicating the elastic properties of rocks.